Sumi-E : Traveling Exhibition of Japanese Contemporary. - Kawakita, Michiaki (Tokyo : Kokusai Bunka Shinkokai, 1962)
Bogart, Alice W. ; Chokai, Seiji ; Fujii, Ikuko ; Fukuda, Heihachiro ; Hidal, Nankoku ; Hidaka, Masakatsu ; Ibaragi, Sampu ; Inoue, Yuichi ; Ito, Shinsui ; Iwasaki, Hajin ; Iwakiri, Gozan ; Iwasaki, Ryou ; Kayama, Matazo ; Kobayashi, Sokyojin ; Komatsu, Hitoshi ; Maeda, Seison ; etc.
Sumi-E Traveling Exhibition of Japanese Contemporary. Organized by Kokusai Bunka Shinkokai, Tokyo (Society for International Cultural Relations), 1962
English
kunstcatalogus
Keywords: Japan